Теплові характеристики вузлів примикання вікон до цегляних та залізобетонних стін цивільних будівель на території Кіровоградської області - Пашинський, В. А.; Джирма, С. О.; Пашинський, М. В.; Pashynskyi, V.; Dzhyrma, S.; Pashynskyi, M.; Пашинский, В. А.; Джирма, С. А.; Пашинский, Н. В. (ЦНТУ, 2020)
Проаналізовані температурні поля вузлів бічного примикання металопластикових віконних блоків до стін житлових і громадських будівель, які зводилися в другій половині минулого століття, а також використовуються в сучасному цивільному будівництві. Моделювання за методом скінченних елементів дозволило визначити найменші температури поверхонь внутрішніх відкосів в кліматичних умовах Кіровоградської області. Для кожного з розглянутих вузлів перевірена можливість утворення конденсату на внутрішніх поверхнях стін з урахуванням положення віконних блоків по товщині стіни. Existing design standards require that the temperature of the inner surface of the enclosure in the zones of high thermal conductivity should not fall below the temperature of the dew point. This phenomenon can occur in a place of window framing to the wall of residential and public buildings, which were massively produced in the second half of the twentieth century. Condensation can be avoided by raising the surface temperature of the inner window jamb extensions. This can be done by adding an additional insulation or displacement of the block frame window inside the building. The aim of the work is to calculate the appropriate values of the displacement of the block frame window inside the wall of different types for the climatic conditions of the Kirovograd region. The framing of metal-plastic windows to the walls of various structures that were produced in the second half of the twentieth century are analyzed. The insulation is performed in accordance with DBN B.2.6- 31-2016. The lowest design temperature of the coldest five-day period within the territory of the Kirovograd Region is -24 °С. As a safety margin, the dew point temperature for residential and public buildings for various purposes is taken to be +11 °C. Finite element modeling in the THERM program environment made it possible to construct the temperature fields of the framing of metal-plastic windows to the walls of various structures and to obtain the very temperature of the inner window jamb extensions at various positions of the window frame within the wall. For each of the nodes examined, the possibility of condensation on the inner surfaces of the walls was established taking into account the position of window frame within the wall. As a result of the studies, it was found that the nodes of the side framing of the windows to the brick and panel walls of civil buildings without additional facade insulation do not meet the requirements for thermal reliability according to the condensation criterion. Facade insulation of existing or new walls, made in accordance with the requirements of DBN B.2.6-31-2016 "Thermal insulation of buildings", in almost all cases guarantees the absence of condensation on the internal surfaces of window jambs. Проанализированы температурные поля узлов бокового примыкания металлопластиковых оконных блоков к стенам жилых и общественных зданий, которые возводились во второй половине прошлого века, а также используются в современном гражданском строительстве. Моделирование методом конечных элементов позволило определить наименьшие температуры поверхностей внутренних откосов в климатических условиях Кировоградской области. Для каждого из рассмотренных узлов проверена возможность образования конденсата на внутренних поверхностях стен с учетом положения оконных блоков по толщине стены.
Thermal Characteristics of Window Junctions to Brick and Reinforced Concrete Walls of Civil Buildings in the Kirovograd Region
Тепловые характеристики узлов примыкания окон к кирпичным и железобетонным стенам гражданских зданий на территории Кировоградской области
Keywords: зовнішні стіни; примикання вікон; температура поверхні; конденсат; outside walls; windows framing; surface temperature; condensation; внешние стены; примыкание окон; температура поверхности; конденсат